Women and Coffee Shops: Negotiation of The Identity of Modernity and Piety in the Sharia Public Space - Mawardi Siregar (Universitas Pendidikan Ganesha, 2023)
Women often get discriminatory treatment in public spaces. Especially in a still strong patriarchal culture, women cannot move in public spaces. There are several studies on the image of Muslim women and their lifestyles, defending the argument about their resistance to the hegemony of religious culture to express a social identity in line with modernity. This paper intends to put forward a different argument. Based on a case study in Langsa, Aceh, this paper discusses how Muslim women negotiate a pious identity and lifestyles based on social practices at coffee shops. Data were collected through observation, interviews, and focus group discussions (FGD) with female consumers, business owners, and coffee shop staff. Using the docile agency proposed by Saba Mahmood, this paper argues that the implementation of Sharia law in Aceh causes young women to have creativity in seeking a synthesis between piety, lifestyle, and modernity. This finding challenges the views of several feminists who claim that the increasing religious performance in the public sphere impacts the marginalization of Muslim women's social identity and autonomy. In contrast to this view, the current study shows the ability of Muslim women in Aceh to find a creative combination of piety, modernity, and a lifestyle that fits their era.